Structural cerebellar correlates of cognitive functions in spinocerebellar ataxia type 2 - Olivito, G.; Lupo, M.; Iacobacci, C.; Clausi, S.; Romano, S.; Masciullo, M.; Molinari, M.; Cercignani, M.; Bozzali, M.; Leggio, M. (Journal of neurology, 2018)
Spinocerebellar ataxia type 2 (SCA2) is an autosomal dominant neurodegenerative disease involving the cerebellum and characterized by a typical motor syndrome. In addition, the presence of cognitive impairment is now widely acknowledged as a feature of SCA2. Given the extensive connections between the cerebellum and associative cerebral areas, it is reasonable to hypothesize that cerebellar neurodegeneration associated with SCA2 may impact on the cerebellar modulation of the cerebral cortex, thus resulting in functional impairment. The aim of the present study was to investigate and quantitatively map the pattern of cerebellar gray matter (GM) atrophy due to SCA2 neurodegeneration and to correlate that with patients’ cognitive performances. Cerebellar GM maps were extracted and compared between SCA2 patients ( n = 9) and controls ( n = 33) by using voxel-based morphometry. Furthermore, the relationship between cerebellar GM atrophy and neuropsychological scores of the patients was assessed. Specific cerebellar GM regions were found to be affected in patients. Additionally, GM loss in cognitive posterior lobules (VI, Crus I, Crus II, VIIB, IX) correlated with visuospatial, verbal memory and executive tasks, while additional correlations with motor anterior (V) and posterior (VIIIA, VIIIB) lobules were found for the tasks engaging motor and planning components. Our results provide evidence that the SCA2 neurodegenerative process affects the cerebellar cortex and that MRI indices of atrophy in different cerebellar subregions may account for the specificity of cognitive symptomatology observed in patients, as result of a cerebello-cerebral dysregulation.